Genetic diversity and comparison of diagnostic tests for characterization of foot‐and‐mouth disease virus strains from Pakistan 2008–2012. Issue 2 (16th October 2017) - Ahmed, Z.; Pauszek, S. J.; Ludi, A.; LaRocco, M.; Khan, E.‐u.‐H.; Afzal, M.; Arshed, M. J.; Farooq, U.; Arzt, J.; Bertram, M.; Brito, B.; Naeem, K.; et al.
Summary: We report the laboratory analysis of 125 clinical samples from suspected cases of foot‐and‐mouth disease (FMD) in cattle and Asian buffalo collected in Pakistan between 2008 and 2012. Of these samples, 89 were found to contain viral RNA by rRT‐PCR, of which 88 were also found to contain infectious FMD virus (FMDV) by virus isolation (VI), with strong correlation between these tests (κ = 0.96). Samples that were VI‐positive were serotyped by antigen detection ELISA (Ag‐ELISA) and VP1 sequence acquisition and analysis. Sequence data identified FMDV serotypes A ( n = 13), O ( n = 36) and Asia‐1 ( n = 41), including three samples from which both serotypes Asia‐1 and O were detected. Serotype A viruses were classified within three different Iran‐05 sublineages: HER‐10, FAR‐11 and ESF‐10. All serotype Asia‐1 were within Group VII (Sindh‐08 lineage), in a genetic clade that differs from viruses isolated prior to 2010. All serotypes O were classified as PanAsia‐2 within two different sublineages: ANT‐10 and BAL‐09. Using VP1 sequencing as the gold standard for serotype determination, the overall sensitivity of Ag‐ELISA to correctly determine serotype was 74%, and serotype‐specific sensitivity was 8% for serotype A, 88% for Asia‐1 and 89% for O. Serotype‐specific specificity was 100% for serotype A, 93% for Asia‐1 and 94% for O. Interestingly, 12 of 13 serotype A viruses were not detected by Ag‐ELISA. This study confirms earlier accounts of regional genetic diversity of FMDV in Pakistan and highlights the importance of continued validation of diagnostic tests for rapidly evolving pathogens such as FMDV.